Potensi Ekstrak Kulit Buah Naga untuk Mitigasi Cekaman Salinitas pada Perkecambahan Benih Kedelai - Maman Suryaman; Ida Hodiyah; Neng Inten (Agrotechnology Research Journal, 2020)
Salinity stress has negative effect on seed germination; therefore, it is necessary to find technology to mitigate it. The research was conducted to study the potency of peel extract of dragon fruit to mitigate salinity stress on soybean seed germination. This research used a randomized block design with factorial patterns and three replications. The first factor was the level of salinity of NaCl (C), consisted of 3 levels (c0 = 0%, c1=0.5%, c2=1%), The second factor was peel extract of dragon fruit (I), consisted of 3 levels (i0 = 0% (control), i1 = 1%, and i2=2%). The parameters analyzed were germination percentage, germination rate, root length, epicotyl length, electric conductivity, and dry weight of sprout. The data were analyzed with ANOVA and Duncan’s multiple range test at α = 5 %. The result showed no interaction between salinity stress and peel extract of dragon fruit on soybean seed germination. Salinity stress significantly decreased sprout vigor with the highest decrease was shown at 1% salinity; on contrarily peel extract of dragon fruit could maintain sprout vigor. Peel extract of dragon fruit 2% was the potential to mitigate salinity stress.